Late Cretaceous stratigraphy and paleoceanographic evolution in the Great Australian Bight Basin based on results from IODP Site U1512 - MacLeod, K. G.; White, L. T.; Wainman, C. C.; Martinez, M.; Jones, M. M.; Batenburg, S. J.; Riquier, L.; Haynes, S. J.; Watkins, D. K.; Bogus, K. A.; Brumsack, H. -J.; do Monte Guerra, R.; et al. (Gondwana Research, 2020)
The Upper Cretaceous sedimentary sequence at International Ocean Discovery Program Site U1512 in the Ceduna Sub-basin of the Great Australian Bight represents a continuous, > 690 m thick interval of black silty clay and claystone spanning the lower Turonian through Lower Campanian (~10 million years). Sediments were deposited in an elongate, ~E-W oriented, ~2500 km long rift system that developed between Australia and Antarctica with an open-ocean connection to the west and a continental bridge to the east. Site U1512 cores provide a unique, continuous record of Late Cretaceous deposition in the Ceduna Sub-basin on the hanging wall of the Wallaroo Fault Zone. Study of U1512 samples could provide both an important high-latitude, southern hemisphere perspective on climatic evolution during the peak and demise of the Cretaceous hothouse and an offshore record of the sedimentation history in the basin during the Late Cretaceous portion of the Gondwanan breakup. The Upper Cretaceous sequence at Site U1512 is notable for its lithologic uniformity. Burrow-mottled to massive claystone and silty claystone make up the majority of the almost 700 m section, while rare (n = 28) isolated, 2 to 21 cm thick medium to fine sandstone beds are a minor lithology. Macrofossils present include common inoceramids and rare occurrences of other bivalves and ammonites. Microfossils include common occurrences of calcareous nannofossils, agglutinated and calcareous benthic foraminifera, radiolaria and organic-walled dinoflagellate cysts as well as rare, small, surface dwelling planktonic foraminifera. Carbonate (<7%) and organic carbon (<1.5%) contents are low. Despite the lithologic uniformity, rhythmic alternations in the intensity of magnetic susceptibility and natural gamma radiation are well-resolved in much of the recovered section and continue through minor coring gaps (as documented by downhole logs). Data from Site U1512 provide new perspectives on the deep-water frontier region between Antarctica and Australia.